Neuropathic pain as independent predictor of worse quality of life in patients with diabetic neuropathy - Vukojević, Zoran; Perić, Stojan; Dominović Kovačević, Aleksandra; Božović, Ivo; Grgic, Sanja; Basta, Ivana; Lavrnić, Dragana (Vojnosanitetski pregled, 2021)
Background/Aim. The prevalence of diabetes mellitus in general population is constantly increasing. On the other hand, the number of diabetic patients with neuropathic pain is large. The aim of the study was to examine influence of neuropathic pain on quality of life (QoL) in patients with diabetic sensorimotor polyneuropathy (DSPN) who did not have any other diabetic complication or any other significant comorbidity. Methods. A total of 32 patients with DSPN and definitive neuropathic pain were compared with 32 patients with DSPN without neuropathic pain. The respondents were matched according to age, gender, and duration of illness. The following scales were used: the Pain Detect Questionnaire, Leeds Assessment of Neuropathic Symptoms and Signs, Douleur Neuropathique EN 4 Questions, Hamilton depression and anxiety rating scales, Neuropathy Impairment Score of the Lower Limb (NIS-LL), and the Short Form 36 Health Survey Questionnaire (SF-36). Results. Patients with neuropathic pain had significantly more severe DSPN measured with NIS-LL (p < 0.01). They were more likely to be engaged in physical work (p < 0.05), and had more symptoms of depression (p < 0.05) than patients without neuropathic pain. Patients with neuropathic pain had significantly lower QoL in both physical and mental domains (p < 0.01). Independent predictors of worse QoL in DSPN were presence of depression (beta=-0.58, p < 0.01) and presence of neuropathic pain (beta = -0.23, p < 0.05) - R2adjusted = 0.48. Conclusion. Independent predictors of QoL in patients with DSPN were presence of depression and neuropathic pain, which signifies importance of their early recognition and early treatment.